Techno-economic potential of waste heat recovery from German energy-intensive industry with Organic Rankine Cycle technology. (December 2020) - Pili, R.; García Martínez, L.; Wieland, C.; Spliethoff, H.
Abstract: Large amounts of waste heat are released unexploited to the environment by industry. In Germany, this sector is responsible for almost one fourth of the total country carbon dioxide emissions. A valuable alternative to recover the waste heat and convert it into electricity is the Organic Rankine Cycle (ORC) technology. In this work, the potential of electricity generation from the waste heat with ORC is assessed for three main industrial sectors: steel manufacturing (basic oxygen furnace, electric arc furnace and reheating furnace for hot rolling mills); cement manufacturing and both hollow and container glass manufacturing. The theoretical, technical and economic potentials are assessed. The estimations are based on the actual production of the industrial sites in Germany and on specific waste heat factors available in literature. The theoretical potential referred to 15 °C amounts to 21–29 TWh/a of waste heat. Because of the limited heat source utilization, efficiency of the ORC and availability, the technical potential of the producible electricity (2.2–4.1 TWhe /a) lies only between 10 and 15% of the theoretical potential. The economic potential, referred to the minimum electricity price in Germany, results in electricity savings of 2.0–3.8 TWhe /a and an ORC cumulative installed capacity of 227–435 MWe . The small difference between the technical and the economical potential confirms the economic viability of the ORC solution, especially in the steel industry. In addition, the ORC plants can contribute to a reduction of 0.9–2.7 Mt CO2 per year. Highlights: Potential of generating electricity from industrial waste heat through the Organic Rankine Cycle. The steel sector has an economic potential of 1.3–2.3 TWhe /a. Cement can contribute with 0.7–1.3 TWhe /a. Glass has a lower economic potential at 0.1–0.4 TWhe /a. The heat recovery from BOF is highly favorable, even for large parameter variation.